Kesulitan Siswa Kelas X MIA SMA Negeri Di Kota Palangka Raya Tahun Ajaran 2018/2019 Dalam Memahami Konsep Struktur Lewis Menggunakan Instrumen Two-Tier Multiple Choice - Elma Kristiana; Suandi Sidauruk; Ruli Meiliawati (FKIP Universitas Palangka Raya, 2020)
Lewis structure is a sub-material that exists in chemical bonding material that is not mastered by students, so a diagnostic test is needed to reveal the difficulties experienced by students. This study aims to describe the difficulties of class X high school students in Palangka Raya City in understanding the concept of Lewis structure which is traced using two tier multiple choice instruments. The subjects of this study were students of class X from Public Senior High School 1 Palangka Raya, Public Senior High School 3 Palangka Raya and Public Senior High School 4 Palangka Raya with the total number of research subjects being 346 students. This research was conducted in the 2018/2019 academic year. Student difficulties were captured using the Lewis Structure Concept Understanding Test (TPKSL) in the form of reasoned multiple choice questions (Two Tier Multiple Choice) and interviews to confirm the difficulties experienced by students. The results showed that the difficulty of students in state high schools in the city of Palangka Raya in understanding the concept of Lewis structure with the smallest to the largest percentage of difficulties was to determine the electron configuration by 65.59%, determine the valence electron by 67.33%, determine the Lewis symbol by 67.33 %, and determine Lewis's structure 69.37%.